Factors affecting preventive behaviors for unplanned pregnancy in female high school students: 10.55131/jphd/2024/220121 - Panpecth, Orathai; Wongsawat, Pramote (Journal of Public Health and Development, 2024)
This cross-sectional study aimed to study the factors affecting preventive behavior for unplanned pregnancy in female high school students. The participants were 498 high school students selected through multi-stage sampling and the sampling of random students from the specified educational levels of Grades 10, 11, and 12 was conducted by using the following inclusion criteria: be a student aged 15-18 years; be a student attending Grade 10, 11, or 12. The data were analyzed by using mean, standard deviation, and binary logistic regression. The results showed that seven factors affected behavior concerning unplanned pregnancy in female high school students including: the educational levels in Grade 12 (OR = 10.65, 95% CI = 1.35 - 83.50), the latest GPA ≥ 3.51 (OR = 9.00, 95% CI = 1.45 - 55.99), the knowledge of birth control (OR = 22.12, 95% CI = 2.43 - 201.81), the attitude toward birth control and pregnancy prevention (OR = 4.15, 95% CI = 1.38 - 12.43), perception of the risk of pregnancy from sexual relationships (OR = 3.79, 95% CI = 1.56 - 9.21), the perception of self-efficacy to prevent pregnancy (OR = 5.31, 95% CI = 2.89 - 9.73), and the self-esteem (OR = 4.24, 95% CI = 1.87 - 9.61). These factors had a 79.10% chance of predicting unplanned pregnancy preventing behaviors in high school students. This study suggests that schools or related organizations should develop health education programs for preventing unplanned pregnancies including knowledge, attitudes, self-efficacy, and self-esteem.